Code Switching and Code Mixing Used in Maudy Ayunda’s YouTube Videos - Trino, Nadiah Abel Ubaidah; Koryati; Evawati, Nian Masna; Zulkifli (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
This final report aimed to identify the types of code-switching and code-mixing. This report analyses Maudy Ayunda’s utterances in her YouTube videos, which contained instances of code-switching and cod emixing, using the audio as the primary data source. The process involved watching and downloading YouTube videos, listening to the speech, transcribing the utterances into a script for data collection, and then analyzing the data using a descriptive qualitative method. The findings indicated three types of code-switching and code-mixing. The code-switching types included tag-switching (5 data), intra-sentential switching (57 data), and inter-sentential switching (20 data). For code-mixing, the types identified were insertion (56 data), alternation (3 data), and congruent lexicalization (5 data). The writers hope this report will provide valuable insights and expand knowledge on bilingualism, code-switching, and code-mixing.